2019
DOI: 10.22159/ajpcr.2018.v12i1.29453
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extract of Date Palm Fruit (Phoenix Dactylifera L.) on Fertility in Male Mice (Mus Musculus L.)

Abstract: Objective: Date palm is one of the plants that have used empirically to increase fertility. Ethanol induction can cause sperm damage in male mice. Sperm damage is one of the infertility agents. The aim of this study was to observe and determine anti-infertility effects of the ethanol extract of date palm fruit in khalal stage in male mice compared with propolis.Methods: A total of 5 groups were assigned to 1 control and 4 experimental groups. Control group was treated by intraperitoneal administration of ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…The Egyptians have been using date palm as a traditional herbal medicine to improve male and female fertility (Hassan et al, 2012). The aqueous extract of P. dactylifera or date palm has been used as a sex enhancer and was shown to cure male infertility which is confirmed by Dillasamola et al (2019). Findings from our present study also supported that P. dactylifera is beneficial in male reproductive system.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The Egyptians have been using date palm as a traditional herbal medicine to improve male and female fertility (Hassan et al, 2012). The aqueous extract of P. dactylifera or date palm has been used as a sex enhancer and was shown to cure male infertility which is confirmed by Dillasamola et al (2019). Findings from our present study also supported that P. dactylifera is beneficial in male reproductive system.…”
Section: Discussionsupporting
confidence: 84%
“…Tauqeer et al (2014) discovered that pollens and fruits of the date palm, have the potential to cure infertility in male and female by increasing the levels of estrogen and testosterone. The administration of ethanol extract of date gave antiinfertility activity to mice, which was characterized by an increase in the number of spermatozoa, the percentage of sperm motility, and weight of the testis (Dillasamola et al, 2019). In line with other studies, Zare et al (2020) demonstrated a significant protective effect of the date fruit extract on sperm parameters and testicular changes in male mice testis-induced formaldehyde toxicity.…”
Section: Introductionsupporting
confidence: 67%